From Elementary Particles to Black Holes (II) - Luangtip, Wasutep; Musiri, Suphot; Pumsa-ard, Kem; Supanam, Nopmanee; Uttayarat, Patipan (Science Essence Journal, 2018)
บทคัดย่อ บทความวิชาการนี้เป็นบทความในส่วนที่ 2 ซึ่งมีเนื้อหาต่อเนื่องจากบทความในส่วนที่ 1 โดยมีจุดมุ่งหมายเพื่อแสดงให้เห็นถึงความสำคัญและบทบาทของฟิสิกส์พลังงานสูงในยุคปัจจุบัน รวมไปถึงความท้าทายที่นักฟิสิกส์กำลังเผชิญอยู่ บทความในส่วนที่ 2 นี้จะกล่าวถึงฟิสิกส์ของหลุมดำ โดยครึ่งแรกของบทความที่ 2 กล่าวถึงทฤษฎีและข้อขัดแย้งของหลุมดำในทฤษฎีสัมพัทธภาพกับทฤษฎีควอนตัม และหลักการการขจัดข้อขัดแย้งดังกล่าวที่มีการเสนอขึ้น ซึ่งอาจใช้เป็นวิธีการพัฒนาทฤษฎีควอมตัม-กราวิตีได้ในอนาคต ในส่วนครึ่งหลังของบทความส่วนที่ 2 ได้กล่าวถึงกระบวนการในการตรวจหาและศึกษาหลุมดำโดยใช้การสังเกตการณ์ทางดาราศาสตร์ รวมไปถึงปริศนาการเปล่งรังสีเอกซ์จากแก๊สรอบๆหลุมดำที่มีความสว่างเกินกว่าปกติ คำสำคัญ: หลุมดำ ระบบดาวคู่ ABSTRACT This article is the second and final part of the two-article-series review on current knowledge in high-energy physics. The present article concerns the physics of black holes. The first part of the article deals with theoretical aspects of black holes and the apparent contradictions between quantum theory and general theory of relativities. Possible resolution, as well as its potential in the development of quantum gravity, is discussed. The second part of the article explains the astronomical methods for observing and studying black holes. It also discusses the puzzle of ultraluminous X-rays emitted from the gas clouds surrounding black holes. Keywords: Black holes, Binary system